The Effectiveness of Free Drawing Activities to Improve Vocabulary and Creativity of Early Childhood - Jarmiati, Jarmiati; Kustiono, Kustiono; Budiartati, Emmy (Journal of Primary Education, 2020)
Vocabulary and creativity are very important to be developed, one of which is through free drawing so that children can express themselves. The design of this study was quasi-experimental, with a form of non-equivalent control group design. The population were all children aged 5-6 years old, Dharma Wanita Kindergarten in Batangan District, Pati Regency. Data sample were Dharma Wanita Bulumulyo Kindergarten amounting to 46 students and Dharma Wanita Ngening Kindergarten totalling 51 students. Simple random sampling technique was used to obtain the samples. Data collection used was non-test techniques, namely observation and documentation. Observations were made to observe the vocabulary and creativity of early childhood before and after treatment. Data analysis used a paired t-test. The results showed that free drawing activities were effective in increasing vocabulary and early childhood creativity. Free drawing can encourage children to describe the pictures that have been made and increase student creativity through exploration of various drawing materials, colors, and imagination.